The demand for speech pathology services for children: Do we need more or just different?. (23rd September 2016) - Reilly, Sheena; Harper, Megan; Goldfeld, Sharon
Abstract: An inability or difficulty communicating can have a profound impact on a child's future ability to participate in society as a productive adult. Over the past few years the number of interventions for children with speech and language problems has almost doubled; the majority are targeted interventions delivered by speech pathologists. In this paper we examine the distribution of speech pathology services in metropolitan Melbourne and how these are aligned with need as defined by vulnerability in language and social disadvantage. We identified three times as many private sector services compared to public services for the 0–5 year age group. Overall there was poorer availability of services in some of the most vulnerable areas. The profound and long‐term impact of impoverished childhood language, coupled with the considerable limitations on public spending, provide a strong impetus to deliver more equitably distributed speech pathology services.